Evaluation of Proximate Composition and Mineral Profile of Raw Milk from Three Livestock Species - Anum , Nishwa; Lashari , Mushtaq Hussain; Riaz, Roshan; Ali, Atiq; Ahmed, Hafiz Saleet; Tahir, Muhammad Naeem (Insights in Animal Science, 2024)
This study investigated the variation in raw milk composition as influenced by species and parity among milking animals. Milk samples from buffalo, cow, and goat were randomly collected from livestock farms across three districts in southern Punjab, Pakistan. Alongside milk sampling, detailed animal-related data, including species and parity, were recorded. The milk samples underwent chemical analysis to determine proximate composition and mineral content. The results revealed significant differences (p < 0.05) in all proximate variables, including total solids, fat, solids-not-fat, and crude protein, among the three species, while parity had no significant effect on these variables. Mineral parameters also varied significantly among species. Buffalo milk demonstrated the highest total solids (15.6%), and fat content (5.4%) compared to cattle (12.3% and 4.0%) and goat milk (12.1% and 3.88%), respectively. However, buffalo milk exhibited the lowest potassium content (37.7 ± 11.76) compared to cattle (60.7 ± 8.68) and goat milk (50.6 ± 8.05 mg/25 mL). Sodium levels were statistically similar across species. Calcium content was significantly higher in goat milk (647.5 ± 32.75 mg/25 mL) compared to buffalo (329.9 ± 44.38 mg/25 mL) and cattle milk (447.8 ± 30.41 mg/25 mL). While buffalo milk contained higher concentrations of major nutrients, it exhibited lower macro-mineral levels. These findings highlight the significant compositional variation in milk among species, providing a basis for selecting milk sources based on nutritional and mineral requirements.
Keywords: milk composition; buffalo; cattle; goat